Dark peptide discs for the investigation of membrane proteins in supported lipid bilayers: the case of synaptobrevin 2 (VAMP2). Issue 21 (20th September 2022) - Luchini, Alessandra; Tidemand, Frederik Grønbæk; Johansen, Nicolai Tidemand; Sebastiani, Federica; Corucci, Giacomo; Fragneto, Giovanna; Cárdenas, Marité; Arleth, Lise
Abstract : Dark peptide discs enable the quantification of membrane protein concentration loaded in the discs. They can also be used to form supported lipid bilayers with oriented membrane proteins, which are advanced model systems mimicking biological membranes. Abstract : Supported lipid bilayers (SLBs) are commonly used as model systems mimicking biological membranes. Recently, we reported a new method to produce SLBs with incorporated membrane proteins, which is based on the application of peptide discs [Luchini et al., Analytical Chemistry, 2020, 92, 1081–1088]. Peptide discs are small discoidal particles composed of a lipid core and an outer belt of self-assembled 18A peptides. SLBs including membrane proteins can be formed by depositing the peptide discs on a solid support and subsequently removing the peptide by buffer rinsing. Here, we introduce a new variant of the 18A peptide, named dark peptide (d18A). d18A exhibits UV absorption at 214 nm, whereas the absorption at 280 nm is negligible. This improves sample preparation as it enables a direct quantification of the membrane protein concentration in the peptide discs by measuring UV absorption at 280 nm. We describe the application of the peptide discs prepared with d18A (dark peptide discs) to produce SLBs with a membrane protein, synaptobrevin 2 (VAMP2). The collected data showed the successful formation of SLBs with high surface coverage and incorporation of VAMP2 in a single orientation with the extramembrane domain exposed towards the bulk solvent. Compared to 18A, we found that d18A was more efficiently removed from the SLB. Our data confirmed the structural organisation of VAMP2 as including both α-helical and β-sheet secondary structure. We further verified the orientation of VAMP2 in the SLBs by characterising the binding of VAMP2 with α-synuclein. These results point at the produced SLBs as relevant membrane models for biophysical studies as well as nanostructured biomaterials.